2016
DOI: 10.1016/j.jpowsour.2016.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Empirical membrane lifetime model for heavy duty fuel cell systems

Abstract: Heavy duty fuel cells used in transportation system applications such as transit buses expose the fuel cell membranes to conditions that can lead to lifetime-limiting membrane failure via combined chemical and mechanical degradation. Highly durable membranes and reliable predictive models are therefore needed in order to achieve the heavy duty fuel cell lifetime target of 18,000 h. In the present work, an empirical membrane lifetime model was developed based on laboratory data from a suite of accelerated membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Generally speaking, oxygen molecule is reduced either by a 2‐e − process to peroxide, or by a 4‐e − process to water . However, the peroxide generated in the 2‐e − process is harmful to the cell assembly and reduces the cell life . Therefore, ORR catalysts with high selectivity toward the 4‐e − process are preferred.…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, oxygen molecule is reduced either by a 2‐e − process to peroxide, or by a 4‐e − process to water . However, the peroxide generated in the 2‐e − process is harmful to the cell assembly and reduces the cell life . Therefore, ORR catalysts with high selectivity toward the 4‐e − process are preferred.…”
Section: Resultsmentioning
confidence: 99%
“…Macauley et al. observed that heavy‐duty fuel cells that were used during a project in Whistler, British Columbia, with 50 fuel cell transit busses reached a lifetime of 17 500 h . This is of the order of magnitude of the target of the Department of Energy (DOE) of 18 000 h for the year 2016 for fuel‐cell power plants .…”
Section: Resultsmentioning
confidence: 99%
“…[47] Manufacturers state lifetimes between 40 000 [48] and 80 000 h. [49] It is, however, crucialt ot ake appropriate maintenance measures with regularc hecks and replacement of wearing parts.I n comparison, lifetimes for fuel cells are reported between 1300 [50] and 87 600 h( 10 years). [50,51] Macauley et al observed that heavy-duty fuel cells that were used during ap roject in Whistler, British Columbia, with 50 fuel cell transit busses reached al ifetime of 17 500 h. [52] This is of the order of magnitude of the target of the Department of Energy (DOE) of 18 000 hfor the year 2016 for fuel-cell powerplants. [53] Manufacturers state lifetimes in the same range.…”
Section: Electrolysis and Fuel Cellmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] High-efficiency type of PEMFC leads to forecasting performance and improve the cell design and all component of the device that combined with it. The power generation process by the fuel cell has performed through electrochemical reactions instead of traditional combustion systems.…”
Section: Introductionmentioning
confidence: 99%
“…The high current density delivered by PEMFC results in the compressed design, fast answer time, and lightweight. [1][2][3][4][5][6][7] High-efficiency type of PEMFC leads to forecasting performance and improve the cell design and all component of the device that combined with it. From witch precision modeling, the price and time decrease in periods of designing and testing is investigated to obtain the extra advantages.…”
Section: Introductionmentioning
confidence: 99%